A Method and Equipment for Continuously Testing the Permeability Coefficient of Rock and Soil Layers - Wei Chen; Datian Cui; Meng Xu; Rongchao Xu (Advances in Civil Engineering)
The water pressure test and steady-flow pumping test are still commonly used for measuring the permeability coefficient of rock and soil strata. Limited by the fact that the average value of the permeability coefficient could be obtained only by this testing method, the accuracy of the experimental results of the permeability coefficient for special rock and soil strata is not good. Therefore, a new on-site testing method and equipment for continuously measuring the permeability coefficient of rock and soil strata is studied in this paper. The method is suitable for water pressure testing in borehole and the steady-flow pumping test. The technical proposal is when the pumping test or water pressure test is carried out, the final water penetration will tend to be a stable value, and then, the high-precision current meter probe will be placed at the bottom of the pumping test hole or water pressure test hole. For the pumping test, the current meter will be lifted uniformly from the bottom of the borehole testing section to the stable water level. Meanwhile, the flow rate of a differential zone of the tested section is continuously detected. For the water pressure test, the current meter will be lifted uniformly from the bottom of the borehole test section to the top of the borehole test section, and the flow rate of the differential section will be continuously detected. Through data analysis and processing, not only the average permeability coefficient of the detected sections can be obtained but also the permeability coefficient of the differential section of the rock and soil stratum can be calculated, respectively. Furthermore, the corresponding relationship between the permeability coefficient and the detected location can be obtained. In view of the abovementioned reasons, the leaking point, the specific position, and the leakage quantity of the detected section could be found out accurately, which will improve the accuracy of the testing results obviously.